The playwright who dramatised his own war record: a reassessment of William Douglas-Home's accounts of his refusal to fight for the liberation of Le Havre. Issue 3 (2nd July 2016) - Luckhurst, Tim; Phippen, Lesley
Abstract: At a court martial in October 1944, William Douglas-Home was convicted of wilfully disobeying a lawful command because he claimed a moral justification to do so. Cashiered and jailed for his offence, he would return to the events that occasioned his refusal throughout a long career as a playwright. In his post-war accounts, Mr Douglas-Home developed a defence of his decision that depicted it as principled. He submitted petitions in which he sought to overturn retrospectively the court martial ruling. This essay argues that he concocted the accounts of his actions on which his efforts to revise the record were based.